A history of the biogeography of Amazonian fishes - Dagosta,Fernando C. P. (2018)
ABSTRACT The history of knowledge about Amazonian biogeography is as rich as its fish community, and a fascinating theme of study in itself. Several current paradigms and controversies about Amazonian fish biogeography are rooted in principles dating from the second half of the 18th to the first half of the 19th centuries. The present work establishes a relationship between current biogeographical ideas and their old predecessors, on the basis of a chronologically-oriented historical continuity analysis. The advent of evolutionary theory has not contributed significantly to a transformation of the knowledge on the biogeography of Amazonian fishes. On the other hand, the two main schools of biogeographical thought (dispersalist and vicariant) had major implications on how Amazonian fish distribution is interpreted. The process was gradual and many hypotheses have combined elements from each of the two schools. Chronologically, practically the entire tradition of Amazonian biogeography takes place within the evolutionary paradigm, although its founder Louis Agassiz was himself an anti-evolutionist. The birth of Amazonian biogeography is Agassiz´s travel in Amazon. That document makes it clear that the author did not consider dispersal as a valid explanation for the biogeographical patterns he found. Later, Carl Eigenmann helps to spread the dispersalist tradition as a model for biogeographical explanations in fish distributions, a phase which lasted until the late 20th century. A major shift occurs with the contributions of Marylin Weitzman, Stanley Weitzman and Richard Vari, who associated the temporal framework of phylogenetic hypotheses with distribution patterns, underscoring the predictive power of vicariant biogeography. The present-day paradigm begins with the work of John Lundberg and attempts to incorporate geomorphological and phylogenetic information into integrative biogeographical hypotheses. Some emblematic problems have delayed proposition of general hypotheses on the phylogenetic biogeography of South American fishes, such as the poor state of knowledge of their species-level systematics; an incomplete distributional record for most species and sparse or non-existent data on the phylogenetic history of most supraspecific taxa. Such drawbacks are now being corrected at a fast pace. Recent advances on geographical distribution and an increasing number of phylogenetic hypotheses will allow unprecedented large-scale biogeographic analyses, including those based on event models and Bayesian inference. Thus, the biogeography of South American fishes, especially Amazonian ones, should soon experiment a new age of progress. The success of that new phase will depend on its ability to recognize and segregate multiple overlapping temporal layers of hydrological changes, and to develop analytical tools that can deal with temporal mixing.